INTENSITAS PENGGUNAAN SMARTPHONE DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PROKRASTINASI AKADEMIK MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS JAMBI ANGKATAN 2022 - Radite, Raihan; Rosmiati, Rosmiati; Sari, Nurmala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic procrastination remains a problem among university students because it can hinder task completion, reduce learning productivity, and increase academic pressure. This study aims to analyze the effect of smartphone usage intensity and peer environment on academic procrastination among 2022 cohort students of the Economic Education Study Program, Faculty of Teacher Training and Education, Universitas Jambi, both partially and simultaneously. This study employed a quantitative approach with an ex post facto design. The population consisted of 104 students, with a sample of 82 students determined using the Slovin formula and proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics, prerequisite tests, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS version 26. The results showed that smartphone usage intensity had a positive and significant effect on academic procrastination, while peer environment had no significant partial effect. Simultaneously, both variables significantly affected academic procrastination with an effective contribution of 36.9%. These findings emphasize the importance of managing smartphone use and strengthening students’ self-regulation.